Assessment of the factors controlling sea ice algal and bacterial production in Dease Strait of the Northwest Passage - Campbell, Karley (Progress in Oceanography, 2016)
Algae and heterotrophic bacteria inhabiting the bottom of sea ice contribute to carbon cycling and food web dynamics in the Arctic marine system. The extent of their influence is dependent on cellular productivity, which is affected by environmental conditions that vary seasonally, between study areas, and with ongoing climate change. In this research, estimates of ice algal and bacterial production are presented for the first time in Dease Strait of the Canadian Arctic Archipelago, and the physical or biological processes affecting production are evaluated. A new incubation method that uses oxygen optodes instead of radioisotopes is developed to quantify gross primary production and net production of the bottom-ice community. It also permits assessment of ice algal photophysiological state through the calculation of photosynthesis-irradiance parameters, which are comparable to commonly reported 14C-based measurements. Production estimates acquired from oxygen optodes, along with separate bacterial production incubations, show that sea ice in Dease Strait is only moderately productive relative to other regions of the Arctic. Algal composition (carbon, nitrogen, chlorophyll a) and photophysiology further indicate that low primary production in the region is due to co-limitation by both light and nitrogen. In comparison, bacterial production is largely affected by the supply of organic carbon substrate from sea ice brines and the smallest size fraction of ice algae (< 0.2 μm). Light, nutrient, as well as salinity conditions influence the taxonomic composition of the ice algal community that is present, where low nitrogen and salinity in Dease Strait appear to favor a community of centric over pennate diatoms when sufficient light is available. Collectively these factors drive biomass accumulation, and determine whether the bottom-ice will be autotrophic (net consume CO2) or heterotrophic (net release CO2). We note the potential for heterotrophic conditions to occur well into the spring season, which challenges ...